JURIDICAL DIMENSION OF FREEDOM RELIGIOUS BELIEFS - Oana ŞARAMET (Supplement of Valahia University Law Study. CONFERENCE PAPER, 2015)
Freedom, in all its dimensions, is one of the fundamental values of any democratic society, for whose recognition, devotion, protection or guarantee, the human being has fought, with guns or word, over the time. The existence, dignity and the development of human personality are conditioned by the recognition through the fundamental laws of the state, by the fundamental rights and freedoms of the citizens, constitutional devotion of these being conditioned by regulatory compliance specific to documents, pacts and international conventions, such as the Universal Declaration of the Human Rights, from the treaties and the regional conventions, such as the European Convention of the Human Rights or the Charter of fundamental rights of the European Union. The freedom of religious beliefs or the religious freedom, dedicated, at an international level, European and national, usually the size of a complex fundamental freedom, namely freedom of thought, of conscience and religious freedom allows every human being to have, to express, to practice that religion, belief, faith that best represents, from a spiritual point of view, as well as choosing not to have, not to express or not to practice any sort of religious belief or faith. The way in which each and every one of us understand, explain and express how we think about the world, how we explain this reality, including from a religious perspective, is a matter exclusively for each of us and not by any legislative regulation. However, even exercising the freedom of religious beliefs cannot lead to lead, in any way, to this freedom and exercising another fundamental freedom. In a world where history tends to repeat itself, oppressing or even suppressing the followers of these beliefs or faiths taking part, unfortunately, with some consistency, the intelligence and dignity of the human beings should prevail, again, for that hatred and religious discrimination could be eliminated.
Keywords: freedom; religious beliefs; faiths; regulations